2015
DOI: 10.1007/s13235-015-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Coalitional Games

Abstract: We introduce the concept of evolutionary coalitional games played in a large population. The members of the population play a strategy chosen from a finite set and interact in randomly formed coalitions. The interactions are described by a multiplayer strategic game. Each coalition generates a total utility, identified with the value of the coalition, and equal to the sum of the payoffs of its all members from the multiplayer game. The total utility is distributed among the coalition members, proportionally to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In particular, we have shown that the structure of the Nash equilibria for the Hawk-Dove and Leader games is identical to that of (Anti-)Coordination Game (see Methods, Proposition 8), which suggests that the transparency has a strong effect on successful strategies in these games as well. As a future work, it would also be interesting to extend the transparent game framework to N-agent interactions [60][61][62], to provide an account of naturalistic dynamics in groups.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we have shown that the structure of the Nash equilibria for the Hawk-Dove and Leader games is identical to that of (Anti-)Coordination Game (see Methods, Proposition 8), which suggests that the transparency has a strong effect on successful strategies in these games as well. As a future work, it would also be interesting to extend the transparent game framework to N-agent interactions [60][61][62], to provide an account of naturalistic dynamics in groups.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be of interest to study structural changes in the social dilemmas, which may result in transforming the dilemmas, cf. e.g., [17]. One could also study in this respect the role of the price of anarchy, the price of stability and other characteristics of the social dilemmas, cf.…”
Section: Discussionmentioning
confidence: 99%
“…We could call such a game the 1 2 -th order A-R dilemma, due to the following arguments: Increasing P D (2) in this game from 3, e.g., to 4, we obtain the zeroth-order A-R dilemma, whereas decreasing P D (2) from 3, e.g., to 2 1 2 , we obtain the first-order A-R game, with two polymorphic equilibria: unstable 2 7 and stable 6 7 . Similarly we could introduce higher-order "fractional" dilemmas, e.g., 1 [17,15,10,9,3,18,13,12,10,2] is a second-order R-R game, with two stable (and one unstable) polymorphic equilibria. The game [20,16,13,11,0,19,18,16,7,3] is a first-order five-person A-A game, with one stable (and two unstable) polymorphic equilibria.…”
Section: Lemma 4 the N-person Social Dilemma IV Is The First-order R-mentioning
confidence: 99%
“…To perform such modeling, prior to formulating the game, we first use stochastic geometry tools [30], [31] to characterize metrics, such as the distribution of distances between MTDs and inter-cluster interference. Then, based on these system parameters, In this section, we propose an evolutionary game [27]- [29], [32]- [35] for clustering an infinite number of MTDs, in order to reduce transmission power for each MTD as well as the number of redundant bits sent to the BS. This approach is fully distributed, as it allows an infinite number of MTDs to self-organize into clusters based on increasing data correlation and reducing transmission power.…”
Section: A Problem Formulationmentioning
confidence: 99%